Effects of nitrogen on growth and physiological traits of feed mulberry under salt stress - Jie Tian; Bingxiang Liu; Qian Guo; Yibo Wu; Jingyan Yang; Bingying Zhang; Hongjiao Li (BMC Plant Biology)
Abstract Soil salinization has emerged as a major concern, significantly limiting agricultural development in China. Nitrogen plays a crucial role in maintaining the cycling of key substances and energy metabolism within plants. When applied under salt stress, nitrogen can mitigate some of the detrimental effects of salinity on plants, thus improving growth performance and physiological resilience under saline conditions. In this study, one-year-old ‘Gui 109’ feed mulberry seedlings were used as experimental material in a hydroponic setup to investigate the impact of varying nitrogen levels on the growth, photosynthetic parameters, and physiological responses of the seedlings under different salinity stress levels. The results indicated that, with increasing nitrogen concentration and prolonged stress duration, the plant height, photosynthetic parameters, antioxidant system, osmotic regulation system of feed mulberry seedlings increased first and then decreased, while the intercellular carbon dioxide concentration decreased first and then increased. Early in the stress period, there were no significant changes in the seedlings’ photosynthetic parameters, but in the later stages, both low- and high-nitrogen treatments caused noticeable alterations. In the early stages, moderate nitrogen application significantly enhanced leaf SOD activity. In the prestress phase, 10 mmol/L nitrogen notably increased fine root POD activity, while in the later stages, this nitrogen concentration significantly increased leaf POD activity. Leaf CAT activity peaked at 10 mmol/L, whereas fine root CAT activity peaked at both 6 mmol/L and 10 mmol/L. MDA content in both leaves and fine roots was highest at 6 mmol/L, and soluble protein, soluble sugar, proline contents were also highest at 6 mmol/L and 10 mmol/L. Correlation analysis revealed strong relationships between various growth and physiological indicators, particularly between photosynthetic parameters, as well as between photosynthetic parameters and the antioxidant and osmotic regulation systems. The correlation between photosynthetic parameters was the strongest, with all coefficients exceeding 0.9. In conclusion, while excessive salinity inhibits the growth and development of feed mulberry, moderate nitrogen application significantly enhances antioxidant enzyme activity in both leaves and fine roots, and increases osmotic regulators, thereby alleviating the detrimental effects of high salinity. However, both low and high nitrogen levels adversely affect photosynthesis, ultimately impairing the growth and physiological development of the seedlings.